Thermal and mechanical properties of composite nanofiber webs and films containing cellulose nanowhiskers - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2013)
In this study, nanocomposites reinforced with cellulose nanowhiskers (CNWs) were prepared by employing three different fabrication methods. These methods include electrospinning of nanofiber webs using a single-component nozzle, electrospinning of nanofiber webs using a coaxial bi-component nozzle, and film casting followed by compression molding. Maleic anhydride grafted elastomeric polymer was used as the polymer matrix. Nanocomposite samples obtained from these three different systems were characterized in terms of morphology, and mechanical and thermal properties. The processing-structure-property relationships of the nanocomposites are discussed in this paper.
Keywords: composite nanofiber with cellulose nanowhiskers; coaxial electrospinning; mechanical properties; thermal and morphological properties; CORE/SHELL FIBERS; FABRICATION; ENCAPSULATION